The Act of Cultural Mediation in Children's Play - Milda Brėdikytė (University of Lower Silesia, 2012)
Classic (non-classic) cultural-historical theory has relatively few theoretical studies on children's play and several basic assumptions are not applied to child play. One of these assumptions is cultural mediation and especially the mechanism of mediation: the relation between ideal and real forms of action. In this article a case of adult-child joint play carried out in the frame of a long-term intervention study is reported. The case study of joint tower building play demonstrates what are the specific requirements of a successful mediator role of an adult in play situation. The main steps of successful adult mediation of play activity are defined.